TRPC-mediated Ca2+ signaling and control of cellular functions. (October 2019) - Curcic, Sanja; Schober, Romana; Schindl, Rainer; Groschner, Klaus
Abstract: Canonical members of the TRP superfamily of ion channels have long been recognized as key elements of Ca 2+ handling in a plethora of cell types. The emerging role of TRPC channels in human physiopathology has generated considerable interest in their pharmacological targeting, which requires detailed understanding of their molecular function. Although consent has been reached that receptor-phospholipase C (PLC) pathways and generation of lipid mediators constitute the prominent upstream signaling process that governs channel activity, multimodal sensing features of TRPC complexes have been demonstrated repeatedly. Downstream signaling by TRPC channels is similarly complex and involves the generation of local and global cellular Ca 2+ rises, which are well-defined in space and time to govern specific cellular functions. These TRPC-mediated Ca 2+ signals rely in part on Ca 2+ permeation through the channels, but are essentially complemented by secondary mechanisms such as Ca 2+ mobilization from storage sites and Na + /Ca 2+ exchange, which involve coordinated interaction with signaling partners. Consequently, the control of cell functions by TRPC molecules is critically determined by dynamic assembly and subcellular targeting of the TRPC complexes. The very recent availability of high-resolution structure information on TRPC channel complexes has paved the way towards a comprehensive understanding of signal transduction by TRPC channels. Here, we summarize current concepts of cation permeation in TRPC complexes, TRPC-mediated shaping of cellular Ca 2+ signals and the associated control of specific cell functions.